On the capacity of multisource non-coherent network coding - Mohajer, S.; Jafari, M.; Diggavi, S.N.; Fragouli, C. (2009 IEEE Information Theory Workshop on Networking and Information Theory, 2009)
We consider multisource non-coherent network coding, where multiple sources send information to one or multiple receivers. We prove that this is equivalent to a ldquosubspacerdquo channel, that takes subspaces as inputs and outputs. We then show that the rate of each individual receiver is upper bounded as delta i (T - delta 1 - delta 2 ), where delta i is what we define to be the ldquodominatingrdquo dimension in the subspace codebook of source i, and T is the ldquocoherencerdquo time of the network.